Assessment of phenotypic diversity of Ñuña, a local common bean (Phaseolus vulgaris L.) from the northern Andes in Peru - Angel Esteban Santa Cruz Padilla; Jorge Luis Vásquez-Orrillo; Ricardo Manuel Bardales-Lozano; Hipolito Murga-Orrillo (Genetic Resources)
Ñuña is a local type of common bean (Phaseolus vulgaris L.) cultivated in the Andean region of Peru. It stands out for its ability to expand and burst when roasted; however, its phenotypic diversity has not yet been fully explored. This study determined the phenotypic variability of Ñuña conserved in the Germplasm Bank of the National Institute of Agrarian Innovation of Peru. The analysis considered qualitative and quantitative traits, using multivariate statistics and comparison of means. Results revealed high phenotypic variability in both qualitative and quantitative traits. In qualitative traits, Multiple Correspondence Analysis found that the dark and light colours of the seed heads contributed most significantly to the variability of the accessions. Phylogenetic hierarchical analysis formed four clusters, representing 37% (I), 4% (II), 7% (III), and 52% (IV) of the accessions, respectively. For quantitative traits, Principal Component Analysis showed no discrimination between regions of origin but indicated a highly positive correlation between leaf length and width, and between pod length and width, as well as seed length, width, thickness and weight. Hierarchical analysis of quantitative characters also formed four clusters, representing 22% (A), 16% (B), 30% (C), and 31% (D) of the accessions, respectively. These clusters, analyzed for means comparison, showed significant differences (p < 0.05) with higher values in cluster B for pod length and width, and seed length, width, thickness and weight. Understanding the variability of the qualitative and quantitative traits of Ñuña is crucial for future genetic improvement studies aimed at achieving cultivars with desirable characteristics.